2020
DOI: 10.1039/d0ta02633f
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst design strategies for stable electrochemical CO2 reduction reaction

Abstract: For practical applications, the deactivation processes of electrocatalysts in electrochemical CO2 reduction reactions have to be addressed by studying recent advances such as exclusion of metal impurity effect, periodic electrochemical activation and active nanocatalyst design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 127 publications
0
41
2
2
Order By: Relevance
“…Some studies even found that metal contaminants can be present due to the dissolution of the oxygen-evolution catalyst at the anode used as the counter electrode for the CO2RR and its subsequent re-deposition at the cathode, where it interferes with the CO2RR activity [63,64]. As stated by Won et al, the deposition of metal impurities is also problematic in the electrocatalytic CO2RR due to the complex steps and the susceptibility of the metal to deposition in the reductive potential environment [64,65].…”
Section: Catalyst Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies even found that metal contaminants can be present due to the dissolution of the oxygen-evolution catalyst at the anode used as the counter electrode for the CO2RR and its subsequent re-deposition at the cathode, where it interferes with the CO2RR activity [63,64]. As stated by Won et al, the deposition of metal impurities is also problematic in the electrocatalytic CO2RR due to the complex steps and the susceptibility of the metal to deposition in the reductive potential environment [64,65].…”
Section: Catalyst Poisoningmentioning
confidence: 99%
“…This strategy is known to provide energetically preferred sites for the adsorption of the desired CO2 reduction intermediate. However, in a reductive environment during electrocatalytic CO2 reduction, nanosized particles seldom succeed in retaining their structure due to the highenergy of the surface compared to the bulk material [64,68]. Although some studies have mentioned the importance of surface reconstructing for providing a fresh available catalyst surface and enhancing its electrochemical characteristics [69], more studies have attributed the observed degradation of catalyst activity and selectivity to transformations of the existing surface that alter the structure of the active sites.…”
Section: Catalyst Restructuringmentioning
confidence: 99%
“…In recent years, several studies were done on various electrocatalysts, but yet, there are problems in Faradaic Efficiency (FE), Current Density (CD), Energy Efficiency, electrocatalyst deactivate, the internal resistance of electrocatalysts, and the potential for scalability to the large sizes without the loss of efficiency, because CO 2 is a thermodynamically stable molecule, it is fully oxidized [3][4][5][6][7][8][9][10][11][12]. A suitable electrocatalyst to reduce CO 2 is necessary to reach a low-cost process with acceptable selectivity and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical reduction of carbon dioxide (CO 2 R) driven by renewable energies to produce valuable commodity chemicals or fuels is commonly regarded as a highly promising strategy to establish a sustainable economy based on a closed carbon cycle. However, an effective development to an industrial scale with reasonable economic viability [1] is still impaired by major challenges including electrolyzer engineering [2] , electrode design [3,4] as well as the search for effective and durable catalyst systems [5] . For the latter, especially noble metal free formulations based on inexpensive and readily available elements are particularly desirable [6]…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] We recently demonstrated that a sequential exchange of sulfur in Fe 4. 5 Ni 4.5 S 8 with selenium favors the formation of CO over H 2 under otherwise identical conditions [9] . Due to the involvement of the reactive metal sites in the electrocatalytic conversion of CO 2 [7,14] , we expected similar effects upon variation of the metal content.…”
Section: Introductionmentioning
confidence: 99%